2009
DOI: 10.1016/j.resuscitation.2009.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of resuscitation outcome in a swine model of VF cardiac arrest: A comparison of VF duration, presence of acute myocardial infarction and VF waveform

Abstract: Introduction Factors that affect resuscitation to a perfusing rhythm (ROSC) following ventricular fibrillation (VF) include untreated VF duration, acute myocardial infarction (AMI), and possibly factors reflected in the VF waveform. We hypothesized that resuscitation of VF to ROSC within 3 min is predicted by the VF waveform, independent of untreated VF duration or presence of acute MI. Methods AMI was induced by the occlusion of the left anterior descending coronary artery. VF was induced in normal (N = 30)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…This relation is (partly) driven by arrest duration, as was shown in a study in animals that reported that an independent association between VF characteristics and shock success could only be demonstrated if VF duration was not included in the multivariate model 6 . As VF duration is often unknown, VF characteristics may be used as indicators of time delay and myocardial metabolic state, and, as such, as predictors of shock success.…”
Section: Vf Waveform Characteristics and Defibrillation Successmentioning
confidence: 92%
See 1 more Smart Citation
“…This relation is (partly) driven by arrest duration, as was shown in a study in animals that reported that an independent association between VF characteristics and shock success could only be demonstrated if VF duration was not included in the multivariate model 6 . As VF duration is often unknown, VF characteristics may be used as indicators of time delay and myocardial metabolic state, and, as such, as predictors of shock success.…”
Section: Vf Waveform Characteristics and Defibrillation Successmentioning
confidence: 92%
“…Whereas coarse VF is often seen in the early course of VF and is associated with successful defibrillation, the VF waveform becomes fine as the duration of VF increases and successful defibrillation becomes less likely 5,6 . With delivery of chest compressions shock success may be improved, and the coarseness of the VF waveform seems to increase concurrently 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…However, factors that influencing VF characteristics might affect the probability of defibrillation success and therefore the performance of predictability of these features. In animal studies, Indik et al[ 24 , 25 ]observed that VF waveform characteristics were altered substantially in animals with myocardial infarction and heart failure compared to structurally normal controls. Olasveengen et al[ 26 ] confirmed that acute myocardial infarction (AMI) patients have depressed AMSA compared to patients without AMI in 101 OHCA victims.…”
Section: Discussionmentioning
confidence: 99%
“…CPR generates significant ECG artifacts that complicate VF waveform analysis. Techniques (all LOE 6) including amplitude spectrum area transformation (AMSA) and scaling exponents have been applied to summarize the ECG waveform. Due to the complexity of these methods, their clinical utility has been restricted to more sophisticated AED's.…”
Section: Monitoring During Cprmentioning
confidence: 99%